Dry resist laser patterning of flexible neural probes with fluidic functionality - Bucherer Andreas; Klein Eric; Paul Oliver; Ruther Patrick (Current Directions in Biomedical Engineering)
Optogenetics enables insights into the development of neural diseases. Custom-designed neural probes are necessary to access targeted brain regions. Multifunctional and mechanically flexible probes with minimal footprint, comprising fluidic channels for drug delivery, light sources for optical stimulation, and micro electrodes for electro-physiological readout are beneficial due to reduced tissue trauma and consequently increased long-term stability. This study introduces a mechanically compliant neural probe that provides microfluidic channels and electrodes arranged close to fluidic outlet ports. The key challenge is to open the fluidic inlet and outlet ports avoiding potential channel clogging. A novel laserbased patterning process is demonstrated using a 248 nm KrF excimer laser. It offers high design flexibility in positioning the fluidic ports along the fluidic channels, as well their contamination-free opening under dry conditions. The laser patterning process applies reflective metal layers inside the fluidic channels, confining the laser ablation to the channel cover, thus minimizing potential damage of the channel substrate. Based on its high reflectivity and correspondingly low absorption and transmission at the applied laser wavelength, aluminium is determined to be the best choice for this protective layer.